(untitled) (International Journal of Innovative Research in Engineering & Management, 2023)
Present trends show that the geometrical configuration of the diagrid structural system to be used for high-rise buildings provides aesthetic potential and structural efficiency. The construction of multi-story buildings is increasing worldwide. To counteract the lateral forces, one of the effective ways is to adopt a Diagrid Structural System which also sums up the aesthetics of the building. Lateral loads in diagrid buildings are resisted by inclined members which are placed at the exterior of the building. In this work, the concrete diagrid structure is analysed and compared with the conventional concrete building according to earthquake conditions. This paper considers G+3, G+11 and G+19 storey RC buildings with plan size 15 m x15 m located in zones II and III for analysis. ETABS 17 software is used for the study of structural members. This paper compares maximum storey displacement, maximum storey drift, storey stiffness, shear force and bending moment with different results.